PERSEPSI WISATAWAN JEPANG TERHADAP KUALITAS PELAYANAN PRAMUWISATA JEPANG PADA PT. JTB BALI - Valentino, Takahide; Sendra, I Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
The purpose of this research is to know how the perception from the tourist to the quality services Japan guide PT. JTB Bali and know complaints from quality service the guide so that the company can improve the quality of their service to the tourists. In this study used primary data and secondary data. The technique of data collection conducted with observation, in-depth interviews and dissemination of the questionnaire. Sampling techniques using a purposive sampling while the data analysis techniques used are qualitative and descriptive analysis with the likert scale. The results of this research, the satisfaction of tourist in positions quite agree because still there is not enough good judgment given by the tourists. In addition the results of interviews conducted with the authors Japan pramuwisata there is still unknown, constraints and complaints pramuwisata so that it affects them when serving the tourists who use the products and services of PT. JTB Bali.